Determinan Tax Avoidance pada Industri Makanan dan Minuman Indonesia : Perspektif Agency Theory dan Corporate Governance - Intan Nuraini; Handriani, Eka; Kurniati, Edy Dwi (Jurnal Ragam Pengabdian, 2026)
Tax avoidance is one of the factors that can reduce government revenue from the taxation sector. This study aims to examine the effect of profitability, capital intensity, liquidity, and firm size on tax avoidance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative approach was employed using secondary data obtained from the companies’ annual financial statements. The sample was selected using purposive sampling, resulting in 45 companies with a total of 180 observations. Data were analyzed using panel data regression with the Random Effect Model (REM). The results indicate that profitability, capital intensity, liquidity, and firm size simultaneously have a significant effect on tax avoidance. Partially, profitability, liquidity, and firm size have a significant negative effect on tax avoidance, while capital intensity has a significant positive effect. These findings suggest that companies with higher profitability, stronger liquidity, and larger firm size tend to be more compliant with tax regulations. In contrast, companies with higher capital intensity are more likely to engage in tax avoidance through the utilization of depreciation expenses on fixed assets. Therefore, corporate financial characteristics play an important role in determining tax avoidance practices.